2003
DOI: 10.1037/0894-4105.17.2.272
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of ongoing responses following frontal, nonfrontal, and basal ganglia lesions.

Abstract: The authors investigated the role of the frontal lobes and the basal ganglia in the inhibition of ongoing responses. Seventeen patients with frontal lesions (FG), 20 patients with lesions outside the frontal cortex (NFG), 8 patients with lesions to the basal ganglia (BG), and 20 orthopedic controls (OG) performed the stop-signal task that allows the estimation of the time it takes to inhibit an ongoing reaction (stop signal reaction time [SSRT]). The FG and the BG showed significantly longer SSRTs than the OG.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
101
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 151 publications
(114 citation statements)
references
References 58 publications
11
101
2
Order By: Relevance
“…Activity here may also reflect conflict monitoring processes given the competing Go and NoGo response demands activated on NoGo trials (Botvinick et al, 2001). The activation observed in subcortical regions is consistent with an increasing appreciation of subcortical involvement in cognitive control and, particularly, in inhibitory control (Middleton and Strick, 2000;Rieger et al, 2003;Saint-Cyr, 2003).…”
Section: Split-group Comparisonssupporting
confidence: 51%
“…Activity here may also reflect conflict monitoring processes given the competing Go and NoGo response demands activated on NoGo trials (Botvinick et al, 2001). The activation observed in subcortical regions is consistent with an increasing appreciation of subcortical involvement in cognitive control and, particularly, in inhibitory control (Middleton and Strick, 2000;Rieger et al, 2003;Saint-Cyr, 2003).…”
Section: Split-group Comparisonssupporting
confidence: 51%
“…In this way, an instruction to forget in an item-method task is analogous to a stop signal in a behavioral countermanding paradigm (for a review, see Logan, 1994). Indeed, eventrelated functional imaging reveals that the same areas in the inferior frontal gyrus that are involved in the cessation of overt responses (e.g., Aron, Fletcher, Bullmore, Sahakian, & Robbins, 2003;Overtoom et al, 2002;Pliszka, Liotti, & Woldorff, 2000;Rieger, Gauggel, & Burmeister, 2003) are more active during the study of an F word that and 2,600 msec after the memory instruction, thereby eliminating the RT disadvantage for post-F versus post-R probe detection.…”
Section: Discussionmentioning
confidence: 99%
“…On forget trials, Wylie et al observed greater activity in inferior frontal gyrus when to-be-forgotten words were later successfully forgotten than when they were recognized. Importantly, regions of the inferior frontal gyrus are also active during the successful stopping of unwanted overt responses (e.g., Aron, Fletcher, Bullmore, Sahakian, & Robbins, 2003;Rieger, Gauggel, & Burmeister, 2003) and have been implicated in the ventral attentional system that is associated with exogenous attention (see Corbetta & Shulman, 2002). If item-method directed forgetting thereby operates in a way that is analogous to motor response inhibition (cf.…”
Section: Discussionmentioning
confidence: 99%